Penerapan Model Problem Based Learning untuk Meningkatkan Kerjasama dan Hasil Belajar Matematika Kelas IV SDN Koroulon 1 - Niken Susilawati; Galih Kusumo (Universitas Maritim AMNI Semarang, 2024)
This study was motivated by the low mathematics learning outcomes and cooperation skills of fourth grade students of SD Negeri Koroulon 1, so the purpose of this study was to improve mathematics learning outcomes and cooperation attitudes of students by using the Problem Based Learning model. The type of research used is Classroom Action Research (PTK) which is carried out in two cycles. the subject of this research is grade IV students. The instruments in this study used test and non-test instruments. Evaluation tests were used to collect data on student learning outcomes, while observation sheet instruments were used to collect data on student cooperation. the results of this study indicate an increase in learning outcomes as seen from the percentage of completeness from 42.1% to 84.2% at the end of cycle II. The increase also occurred in the average value of student cooperation from 51.2 to 74.89 at the end of cycle II. Based on these results, it can be concluded that the Problem Based Learning model can improve students' math learning outcomes and cooperation.